Modeling And Simulation Of Reactive Distillation Column For The Production Of Dimethyl Carbonate (DMC) - Low, Pui San (Universiti Sains Malaysia, 2018)
The main objective of this research is to develop a simulation model of reactive distillation column for the production of dimethyl carbonate using Aspen Plus as a modeling platform. In this research, the effects that influenced the design and operating condition of the column were also studied. It started with verify the mathematical models that suitable for the simulation software which is Aspen Plus. The proposed model was validated by comparing the simulated results obtained from the published data from literature and with results from Aspen Plus. Analysis and comparison has been performed after the simulation complete and converges. The performance of reactive distillation column was obtained by determining the optimum column configuration and operating conditions at 333K, 1 atm. A propylene carbonate conversion up to 94% was obtained through simulation with the optimized column parameter.